2019
DOI: 10.1101/824763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synchronous chromosome segregation in mouse oocytes is ensured by biphasic securin destruction and cyclin B1-Cdk1

Abstract: Successful cell division relies on the faithful segregation of chromosomes. 13 If chromosomes segregate prematurely the cell is at risk of aneuploidy. Alternatively, 14 if cell division is attempted in the absence of complete chromosome segregation, non-15 segregated chromosomes can become trapped within the cleavage furrow and the cell 16 can lose viability. Securin plays a key role in this process, acting as a pseudosubstrate 17 to inhibit the protease separase that functions to cleave the cohesin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
(72 reference statements)
1
4
0
Order By: Relevance
“…It was shown that securin is required for separase localization to the spindle (Kumada et al, 1998;Jensen et al, 2001). Also measuring the separase activity by a FRET sensor showed that the separase is activated in oocyte meiosis I tens of minutes before anaphase (Nikalayevich et al, 2018;Karasu et al, 2019;Thomas et al, 2019), which is in accordance with the loss of the securin signal on the spindle observed in our experiments. To evaluate whether the accumulation of securin on the spindle has functional significance will require additional experimental work.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It was shown that securin is required for separase localization to the spindle (Kumada et al, 1998;Jensen et al, 2001). Also measuring the separase activity by a FRET sensor showed that the separase is activated in oocyte meiosis I tens of minutes before anaphase (Nikalayevich et al, 2018;Karasu et al, 2019;Thomas et al, 2019), which is in accordance with the loss of the securin signal on the spindle observed in our experiments. To evaluate whether the accumulation of securin on the spindle has functional significance will require additional experimental work.…”
Section: Discussionsupporting
confidence: 89%
“…It is conceivable that there is also an excess of separase in meiosis I, and then the extra securin is required to equilibrate this. It is also possible that securin is required as a substrate of APC/C in meiosis I, as a part of APC/C activity control ( Thomas et al, 2019 ). Administration of fresh cRNA into meiosis II oocytes increases the securin levels on average three times ( Figure 2C ), indicating that the lower expression of securin in meiosis II might be due to a lack of mRNA rather than subject of specific regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mouse oocytes, the APC/C ubiquitylates free Cyclin B1 and Securin before targeting the proteins in complexes (Securin with Separase and Cyclin B1 with Cdk1). Also, their degradation happens prior to all kinetochores being perfectly attached and SAC proteins being completely removed [61,62]. This means that some APC/C activity towards Cyclin B1 and Securin is already present in oocytes before the SAC is silenced [63].…”
Section: The Spindle Assembly Checkpoint and Pp2a-b56 In Oocyte Meiosis Imentioning
confidence: 99%
“…However, the protection of the bound fraction of Securin depends on the dephosphorylation of Securin by PP2A-B56, that protects it from the APC/C, when bound to Separase [64]. However, the preferential degradation of free Securin and Cyclin B1 in mouse oocytes is regulated in a distinct manner-this activity is independent of SAC control and phosphoregulation [62], and specific to oocytes.…”
Section: The Spindle Assembly Checkpoint and Pp2a-b56 In Oocyte Meiosis Imentioning
confidence: 99%